Enhanced Proton Conductivity in Y‐Doped BaZrO3 via Strain Engineering. Issue 12 (27th October 2017) - Fluri, Aline; Marcolongo, Aris; Roddatis, Vladimir; Wokaun, Alexander; Pergolesi, Daniele; Marzari, Nicola; Lippert, Thomas
Abstract: The effects of stress‐induced lattice distortions (strain) on the conductivity of Y‐doped BaZrO3, a high‐temperature proton conductor with key technological applications for sustainable electrochemical energy conversion, are studied. Highly ordered epitaxial thin films are grown in different strain states while monitoring the stress generation and evolution in situ. Enhanced proton conductivity due to lower activation energies is discovered under controlled conditions of tensile strain. In particular, a twofold increased conductivity is measured at 200 °C along a 0.7% tensile strained lattice. This is at variance with conclusions coming from force‐field simulations or the static calculations of diffusion barriers. Here, extensive first‐principles molecular dynamic simulations of proton diffusivity in the proton‐trapping regime are therefore performed and found to agree with the experiments. The simulations highlight that compressive strain confines protons in planes parallel to the substrate, while tensile strain boosts diffusivity in the perpendicular direction, with the net result that the overall conductivity is enhanced. It is indeed the presence of the dopant and the proton‐trapping effect that makes tensile strain favorable for proton conduction. Abstract : Tensile lattice strain is shown for the first time to enhance the proton conduction in the grain interior, which is in contradiction to previous theoretical simulations. Through the synergy of experiment and theory, a new approach to the theoretical modeling of the proton conduction mechanism is developed, which is capable of explaining the experimental results.